DESIGN MODEL OF MOBILE LEARNING IN DISTANCE LEARNING SYSTEM "KHERSON VIRTUAL UNIVERSITY" - Gnedkova, О.О.; Lukutin, В.В. (Journal of Information Technologies in Education (ITE), 2015)
Due to the global process of information of society and the involvement of information and communication technologies (ICT) in all areas of human activity, including in the educational process of high school the paradigm of educational process is changing, priority of human life in the information society presents an opportunity to study anywhere and anytime. This opportunity is provided by many techniques of teaching using ICT, particularly through technology of mobile learning.This learning technology is a new form of learning with the usage of IKT and hasn’t study fully from the methodological point of view, so the question of further development and implementation of mobile learning technologies in educational process of high school is arisen.The implementation of mobile learning technologies in educational practice requires the design of model, which will show the interaction of mobile learning components and distance learning system.The paper proposes a model of interaction between participants of the educational process and technologies of mobile learning based on distance learning system «Kherson Virtual University". The description of the proposed model in terms of the methodological realization in the learning process is presented. In the article the main approaches to the definition of "mobile learning", "environment","educational space", "educational environment", "learning environment" and the implementation process of mobile learning are considered, and the draft of model of mobile learning in the system of distance learning "Kherson Virtual University" is presented.